Pengembangan Perekonomian yang Berbasis Potensi Lokal di Kabupaten Bone - Mirna Mirna (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2019)
This study aims to determine the efforts of local governments in the development of agricultural economics in Bone regency in improving the productivity and quality of food crops in Bone Regency and how factors can influence this development. The research method used is a qualitative research method with descriptive type. Data collection uses library study techniques, observation, interviews, and online data search. Furthermore, the data were analyzed qualitatively. The results showed the stability of economic development in the agricultural sector in Bone Regency can be said that every year agricultural production experienced an increase and also a decline, and instability occurred in every District in Bone Regency. Based on the case, the Bone District government made an effort to increase agricultural production and productivity with various Government programs run by the related Service. The results of this study also show that there are several potential sectors that can be developed in Bone Regency namely Rice, Corn, Soybeans as the three leading sectors that have been developed in the last five years.